Investigating the association between Personality Traits and Mental Health with Accidental proneness - Hamidreza Pouragha; Hassan Ashayeri; Abbas Rahimi Foroushani; Mahsa Naserpour; SJ Shahtaheri (International Journal of Occupational Hygiene, 2020)
Abstract